BRAIN GYM TERHADAP TINGKAT STRES PADA MAHASISWA PROGRAM STUDI ILMU KEPERAWATAN FAKULTAS ILMU KESEHATAN UNIVERSITAS KADIRI - Rahayu, Kun Ika Nur (Dunia Keperawatan: Jurnal Keperawatan dan Kesehatan, 2017)
Students experience stress from various sources. One of the sources is academic problemswhich is associated with the failure of students in completing the academic demands. Thesurvey is done by 20 student of nursing departemen in the eight semester showed that 11 ofthem got stress in medium level and 9 stress in low level. One method to reduce srtess is tobrain gym. The aim of this study was to determine the effect of exercise on the brain towardsstress level on nursing students VIII semester of the Faculty of Health Science, University ofKadiri. A pre-post quasy experimental control group design was used in this study withRandom sampling technique of all ofnursing students VIII semester of the Faculty of HealthScience, University of Kadiri. The result of post test for threatment froup used Wilcoxon testwas gotten P-value 0,025 while for control group was gotten p-value = 0,157. The analyzeresult used Man Whitney with P-value = 0,032 with α = 0,05. It showed there is an influenceof brain gym toward stress level of nursing students in eight semester of Health ScienceFaculty of Kadiri University. The motion of brain gym can activate neocortex andparasympathy nerve to reduce the increase of adrenalin hormon in the body.